DETERMINAN PENYALURAN KREDIT PEMILIKAN RUMAH (KPR) DI INDONESIA (PERIODE 2012-2021) - Adelia, Putri; Al Muizzuddin Fazaalloh (Contemporary Studies in Economic, Finance and Banking, 2023)
People nowadays still consider banks as more reliable sources of capital and media for house ownership loan (KPR) distribution than non-bank financial institutions. The amount of the distributed housing loan increases in every year. The positive trend occurs because there are more people who need housings. The objective of this study is to identify the effects of the regulation of Bank Indonesia that is run through the LTV policies to control KPR and the effect of property prices, inflation, loan interest rate, and economic growth on KPR distribution. This quantitative research uses the Error Correction Model (ECM) – two-step Engle Granger method in EViews 9 in analyzing the data of 2012-2021 period. This research finds that, in the short run, only does economic growth positively and significantly influence the KPR distribution. Then, in the long run, property prices, loan interest rate, and economic growth significantly affect the KPR distribution.